Epiploic Appendagitis masquerading as acute appendicitis. (August 2017) - Menon, Gautam; Menon, Arathi; Menon, Jay
Abstract : Introduction: Epiploic appendagitis is considered as a relatively uncommon surgical condition. We report our observational study which suggest that it is more common that appreciated. Case description: In a weekend on call, out of 4 patients undergoing diagnostic laparoscopy for suspected appendicitis, we encountered 2 clear cases of epiploic appendagitis. These patients had CT scan suggestive of inflammatory process in right iliac fossa; the inflammatory markers were elevated. Diagnostic laparoscopy revealed appendage epilpoicae as the culprit. Results and conclusions: Patients underwent appendicectomy and excision of the appendage with resolution of the symptoms. We conclude that this entity is much more common that appreciated. In cases of serosanguinous fluid in the abdomen and normal looking appendix, search should be undertaken not to overlook a torted appendage. Take-home message: The patients with epiploic appendagitis tend to look well; they are excruciately tender in the area overlying the appendage. Though self-resolving, if identified, the best option is to excise the appendage for early resolution of the symptoms.